Status of Organization Citizen Behavior (OCB) in Nepalese Commercial Banks - Niroula, Khagendra Bahadur; Chamlagai, Ganga Prasad (Dristikon: A Multidisciplinary Journal, 2020)
The paper aims to analyze the status of organization citizen behavior in Nepalese Commercial Banks. This study is based on Likert scale data. Twenty-seven questions are entertained in the set of questionnaires containing major demographic variables such as gender, experience, designation and qualifications of employees in sampled commercial banks. Primary data are collected through convenient and snowball sampling. Collected data are analyzed by using descriptive statistics, Karl Pearson coefficient of correlation, regression model by Andrew Haney’s and Welch‘s ANOVA. The Statistical Package for Social Science (SPSS) 25 versions is used for the analysis of data. The result indicates that OCB favorably exits in Nepalese commercial banks. All dimensions of OCB have positive correlations among each other. The Welch’s ANOVA posits that all employees of commercial banks have same levels of OCB irrespective of their nature. Further, the study proves that OCB at individual and organizational level significantly impact the composite OCB. Gender and education strengthen the relationship between OCB at individual level and composite OCB but these and other variables do not influence in the relationship of OCB at organizational level and composite OCB.